Non-Additive Effects of Repetitive Administration of Lipoplexes in Immunocompetent Mice - Betker, Jamie L. (J Pharm Sci, 2016)
Repetitive administration is routinely used to maintain therapeutic drug levels, but previous studies have documented an accelerated blood clearance of some lipid-based delivery systems under these conditions. To assess the effect of repetitive administration, non-PEGylated lipoplexes (+/− = 0.5) were administered four times via tail vein injection at 3-day intervals to immunocompetent Balb/c mice bearing 4T1 tumors. This study measured the effect of repeat administration of non-targeted lipoplexes on clearance, cytokine/chemokine response, plasmid distribution, reporter gene expression, and liver toxicity. We do not observe a refractory period or a statistically significant difference in blood clearance between the first administration and subsequent injections of this lipoplex formulation, consistent with the absence of a cytokine/chemokine response. However, we do see a significant effect on both plasmid accumulation and expression; an enhancement of 26-fold and 10-fold in tumor plasmid levels and expression, respectively, after 4 injections as compared to that after a single injection. In addition, in vivo imaging suggests that expression in other organs had diminished rapidly 72 h after each administration, in contrast to relatively constant expression in the tumor. Taken together, the findings indicate that gene delivery to tumors can be dramatically enhanced by employing repetitive administration.